Myelin sheaths can act as compact temporary oxygen storage units as modeled by an electrical RC circuit model - Wouter Vervust; Sina Safaei; Katja Witschas; Luc Leybaert; An Ghysels (Proceedings of the National Academy of Sciences, 2025)
Oxygen is crucial for mitochondrial energy production in neurons and is efficiently stored and transported within the hydrophobic core of phospholipid bilayers. Using a diffusive model derived from molecular dynamics simulations, we demonstrate that oxygen storage in a bilayer follows first-order kinetics, which can be effectively represented by an RC (resistor–capacitor) circuit. For myelin, with multiple bilayers, oxygen transport is modeled through a ladder network of RC circuits, where oxygen permeation resistance and oxygen storage capacity scale linearly with bilayer count. Meanwhile, the characteristic time constant scales quadratically with myelin thickness, e.g. enhancing the characteristic time constant from 30 ns for one 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayer to 506 μ s for 200 POPC bilayers. This model shows that myelin sheaths serve as compact oxygen reservoirs, dampening sudden oxygen changes due to their slower release kinetics. During increased neuronal activity, the model suggests that myelination extends the ability to sustain elevated oxygen demand, implying a buffering role for myelin against oxygen fluctuations, while the need for vascular response remains critical in maintaining long-term oxygen homeostasis.